2011
DOI: 10.1109/lsp.2011.2157820
|View full text |Cite
|
Sign up to set email alerts
|

Regularized Subspace Gaussian Mixture Models for Speech Recognition

Abstract: Abstract-We investigate cross-lingual acoustic modelling for low resource languages using the subspace Gaussian mixture model (SGMM). We assume the presence of acoustic models trained on multiple source languages, and use the global subspace parameters from those models for improved modelling in a target language with limited amounts of transcribed speech. Experiments on the GlobalPhone corpus using Spanish, Portuguese, and Swedish as source languages and German as target language (with 1 hour and 5 hours of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 16 publications
2
31
0
1
Order By: Relevance
“…After increasing the amount of training data to be 15 hours, we did not obtain improvement by applying the 1 -norm regularization as shown in Figure 6. This agrees with our previous experience of using 1 -norm regularization for SGMMs [30] on a different task.…”
Section: Cross-lingual Experiments: With Regularizationsupporting
confidence: 92%
See 2 more Smart Citations
“…After increasing the amount of training data to be 15 hours, we did not obtain improvement by applying the 1 -norm regularization as shown in Figure 6. This agrees with our previous experience of using 1 -norm regularization for SGMMs [30] on a different task.…”
Section: Cross-lingual Experiments: With Regularizationsupporting
confidence: 92%
“…This problem is most acute for the state-dependent vectors v jk -unlike the globally shared parameters Φ i , they are only trained on those speech frames which align with the corresponding sub-state. To overcome this problem, we proposed a regularized ML estimate for the state vectors [30] in which penalties based on the 1 -norm and 2 -norm of the state vectors, as well as their linear combination (the elastic net [31]), were investigated. Regularization using the 1 -norm penalty was found to be best suited in cross-lingual settings where the amount of target training data is very limited [28].…”
Section: B Regularized Model Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the performance differences are purely owing to better parameter estimation. For SGMM systems with S = 40, regularized state vector estimation by 1-norm penalty [10] is applied to improve numerical stability; we have also observed that such regularisation brings gains in accuracy [3]. For comparison, the monolingual GMM and SGMM systems with the entire 14.8 hours of target language training data available in GlobalPhone achieve 25.7% and 24.0% WER 2 .…”
Section: Baseline Resultsmentioning
confidence: 95%
“…Em [170] foi proposta uma outra alternativa para compensar modelos baseada na mistura de Gaussianas. Essa técnica, chamada subspace gaussian mixture models (SGMM), utiliza um modelo de subespaços globalmente compartilhado entre os estados, de forma a capturar as maiores virações do modelo, provendo uma representação compacta dos modelos acústicos resultando em uma estimativa robusta de atributos, o que permite obter melhoras no desempenho dos sistemas de reconhecimento.…”
Section: Técnicas De Compensação De Modelosunclassified